PENGARUH MODEL ACTIVE LEARNING TIPE CARD SORT TERHADAP HASIL BELAJAR IPAS DISEKOLAH DASAR - Sonia Nopita Sari; Dian Samitra; Andri Valen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the existence of problems, namely teachers still teach using conventional models with lecture methods, questions and answers, discussions, and groups. The purpose of determine the effect of the Active Learning Card Sort Type model on the learning outcomes of fourth grade students of SD Negeri 11 Lubuklinggau. This type of research is quantitative research. The sample of this study consists of two groups, namely the experimental class which is given active learning model treatment and the control class will be given treatment with conventional learning or lectures. The research population is class IV of SD Negeri 11 as many as 2 classes consisting of class A, namely 24 students and class B of 24 students. The research method is quasi-experimental design with a pretest-posttest control group design. The data collection technique uses a multiple choice test of 15 questions. The instrument that has met the requirements as a measurement requirement, because it has been tested so that it has met the requirements for validity and reliability tests. Based on the results of the study, it shows that there is a significant influence on the learning outcomes of social studies as evidenced by using the t-test, obtained t_(count) 3.27. t_(tabel) with dk-46. So, the value of t_(tabel) = 1.678. The magnitude of the influence of the Active Learning Card Sort Type learning model on conventional learning model.